Fabrication of precisely aligned microwire and microchannel structures: Toward heat stimulation of guided neurites in neuronal cultures. Issue 9 (31st January 2017) - Dang, Ka My; Rinklin, Philipp; Schnitker, Jan; Haberkorn, Bastian; Zobel, Kathrin; Gribaudo, Simona; Perrier, Anselme L.; Carolus, Jorne; Daenen, Michaël; Weigel, Stefan; Luksch, Harald; Offenhäusser, Andreas; et al.
Abstract : Microwire arrays are a powerful tool for the exertion of localized thermal stress on cellular networks. Combining microwire arrays with a set of orthogonal axon‐guiding microchannels on‐chip allows for the positioning of neurites, as well as control over their polarity. In this paper, we present a new fabrication approach, based on standard clean room fabrication and sacrificial layer etching, for the integration of microwire arrays into neurite guiding structures. The system permits the application of strong temperature gradients, enabling localized thermal stimulation inside microchannels.